Genotype-Phenotype Interaction Analyses in Hemophilia - Jaloma-Cruz, Ana Rebeca; Beltrán-Miranda, Claudia Patricia; González-Ramos, Isaura Araceli; López-Jiménez, José de Jesús; Luna-Záizar, Hilda; Mantilla-Capacho, Johanna Milena; Mundo-Ayala, Jessica Noemi; Galván, Mayra Judith Valdés (IntechOpen, 2012)
None